Pull-down Assay on Streptavidin Beads and Surface Plasmon Resonance Chips for SWATH-MS-based Interactomics - Maryáš, Josef; Faktor, Jakub; Čápková, Lenka; Müller, Petr; Skládal, Petr; Bouchal, Pavel (Cancer genomics & proteomics, 2018)
BACKGROUND/AIM: Pul-down assay is a popular in vitro method for identification of physical interactors of selected proteins. Here, for the first time, we compared three conventional variants of pull-down assay with the streptavidin-modified surface plasmon resonance (SPR) chips for the detection of PDZ and LIM domain protein 2 (PDLIM2) interaction partners. MATERIALS AND METHODS: PDLIM2 protein-protein interactions were analysed by three variants of pull-down assay on streptavidin beads using LC-MS/MS in "Sequential Window Acquisition of all Theoretical fragment ion spectra (SWATH)" mode and compared with LC-SWATH-MS/MS data from SPR chips. RESULTS: The results showed that (i) the use of SPR chip led to comparable data compared to on-column streptavidin beads, (ii) gravity flow and microflow in wash and elution steps provided better results than centrifugation, and (iii) type and concentration of detergent did not significantly affect the interactome data of cancer-associated PDLIM2. CONCLUSION: Our study supports further application of SPR-based affinity purification with SWATH mass spectrometry for reproducible and controlled characterization of cancer-associated interactomes.
Keywords: LC-SWATH-MS/MS; Streptavidin; protein-protein interactions; PDLIM2; pull-down assay; Surface Plasmon Resonance; streptavidin; Neoplasms; LIM Domain Proteins; Humans; Protein Interaction Domains and Motifs; SPR; Tandem Mass Spectrometry; nádory; mikrofilamentové proteiny; chromatografie kapalinová; interakční proteinové domény a motivy; tandemová hmotnostní spektrometrie; proteiny s doménou LIM; povrchová plasmonová rezonance; Chromatography, Liquid; Microfilament Proteins; lidé